Process of Granting Retitution Rights to Child victims of crime (study of besilam village langkat district) - Lidya Rahmadani Hasibuan; Hasdiana Juwita Bintang; Nurbela Br. Purba (Yayasan Multidimensi Kreatif, 2024)
One form of compensation for victims of criminal acts is restitution. Restitution in accordance with the Principle of Restoration to its Original Condition (restutio in integrum) is an effort that ensures that crime victims must be returned to their original condition before the crime occurred, even though it is based on the fact that it is impossible for the victim to return to their original condition. This principle emphasizes that the form of recovery for victims must be as complete as possible and cover various aspects arising from the consequences of the crime. With restitution, victims can have their freedom, legal rights, social status, family life and citizenship restored, returned to their place of residence, their job restored, and their assets restored. Restitution itself is defined as the payment of compensation charged to the perpetrator based on a court decision which has permanent legal force for material and/or immaterial losses suffered by the victim or his heirs. For this reason, the perpetrator is required to pay restitution to the child victim of a crime to compensate for the losses suffered by the victim as a form of the perpetrator's responsibility for his actions which caused harm to the victim, his family or his heirs, as the implementation of Article 71 D Paragraph (2) of Law Number 35 of 2014 concerning Amendments to Law number 23 of 2002 concerning Child Protection. Applications for restitution can be submitted by child victims of criminal acts who must be accompanied by parents/guardians, their heirs or through the Institution witness and victim protection. To apply for this restitution, it is hoped that the child's companions have equipped themselves with the applicant's identity file, the identity of the perpetrator, a description of the criminal act, a description of the losses suffered, the amount of restitution requested and the form of restitution requested.